Novel carrier of grafted alginate for covalent immobilization of inulinase - Elnashar, Magdy; Danial, E.; Awad, G. (American Chemical Society, 2009)
Inulinase has been extracted from Penicillium chrysogenum P36 and immobilized on a novel matrix of grafted biopolymer. The crude enzyme has been characterized in terms of specific activity, optimum temperature, and temperature stabilities. A novel matrix of alginate modified with polyimines and cross-linked with glutaraldehyde was prepared in beads shape using the Encapsulator to covalently immobilize crude inulinase. The modified beads were characterized using the FTIR and the DSC techniques. The FTIR showed the presence of the aldehydic's carbonyl group at 1670 cm-1, which differs from that of the carboxylic group at 1620 cm-1. The DSC revealed a significant improvement of the gel's thermal stability from 200 to 240°C. The immobilization process improved the enzyme's optimum temperature from 50 to 55°C as well as the enzyme's thermal stability for 2 h at 60°C with 78% retention of activity as compared to only 7% for the free enzyme. The enzyme's optimum pH slightly shifted from pH 4.8 for the free enzyme to pH 5 for the immobilized enzyme. However, at pH 5.2-5.5, the enzyme activity improved from 39% for the free enzyme to 75% for the immobilized enzyme. The novel matrix successfully immobilized the inulinase covalently with an enzyme loading capacity of 461 U/g gel. The reusability test proved the durability of the grafted alginate for 20 cycles with retention of 95% of the immobilized enzyme activity, whereas the untreated alginate gel completely dissolved by the eighth use. The results were promising; the grafting method is simple, and immobilization efficiency and enzyme loading capacity could be further improved by optimizing the gel beads' formulations and the conditions of immobilization for the industrial applications. © 2009 American Chemical Society.